A Commentary on “Effective Dose of Epidural Hydromorphone for Analgesia Following Caesarean Section in Using Modified Dixon Sequential Method” [Letter] - Wu S; Zhao Y; Li J (Journal of Pain Research)
Sitong Wu,1 Yu Zhao,2 Jin Li3 1College of Integrated Traditional Chinese and Western Medicine of Liaoning University of Traditional Chinese Medicine Shenyang, Liaoning, Shenyang, 110847, People’s Republic of China; 2College of Traditional Chinese Medicine, Liaoning University of Traditional Chinese Medicine, Liaoning, Shenyang, 110847, People’s Republic of China; 3The University Development Research Center of Liaoning University of Traditional Chinese Medicine, Liaoning, Shenyang, 110847, People’s Republic of ChinaCorrespondence: Jin Li, Email 604245409@qq.com